Genome wide characterization of the SERK/SERL gene family in Phalaenopsis equestris, Dendrobium catenatum and Apostasia shenzhenica (Orchidaceae). (April 2020) - Ghai, Devina; Alok, Anshu; Himani,; Upadhyay, S.K.; Sembi, Jaspreet K.
Graphical abstract: Highlights: SERKs play a significant role in morphogenesis, stress/defense and signal transduction. Phalaenopsis equestris & Dendrobium catenatum : 2 SERK & 11 SERLs ; Apostasia shenzhenica : 1 SERK & 8 SERL s . Conserved domains: Signal peptide, leucine zipper, 5 LRRs, SPP, transmembrane domain, kinase, C-terminal. Clustering of SERKs and SERLs in distinct clades in Phylogenetic tree. SERKs showed higher expression in the reproductive tissues than in vegetative tissues. Abstract: Somatic embryogenesis receptor kinases ( SERK s) play a significant role in morphogenesis, stress/defense and signal transduction. In the present study, we have identified two SERK and 11 SERK-like ( SERL ) genes in Phalaenopsis equestris, two SERK and 11 SERL genes in Dendrobium catenatum, and one SERK and eight SERL genes in Apostasia shenzhenica genome. Characterization of the SERK proteins revealed the presence of a signal peptide, a leucine zipper, five leucine-rich repeats (LRRs), a serine proline proline (SPP) motif, a transmembrane region, a kinase domain, and a C-terminus. Most of the SERK/SERL proteins were characterized with similar physicochemical properties. The presence of transmembrane region predicted their membranous localization. Tertiary structure prediction of all the five identified SERK proteins had sequence identity with BAK1 protein of Arabidopsis thaliana . Generally, all the SERK/SERL genes shared similar gene architecture and intron phasing. Gene ontology analysis indicated the role of SERKs in receptor and ATP binding, signal transduction, and protein phosphorylation. Phylogenetic analysis revealed the clustering of SERKs and SERLs in distinct clades. Expression of SERK s in reproductive tissues like floral bud, floral stalk, whole flower and pollen was reported to be higher than their expression in vegetative tissues with an exception of PeSERK1 and DcSERK1 which showed higher expression in leaves and roots, respectively. Likewise, a higher expression of AsSERK1 was observed in tubers. However, lower expression of SERL s was observed in majority of tissues studied irrespective of their vegetative or reproductive origin. This work paves way for future studies involving functional characterization of SERK/SERLs and their potential role in embryogenesis/organogenesis as an aid to regeneration and multiplication of endangered orchids.